The impact of Covid-19 pandemic on financial performance: the case of Singapore listed companies - Htun, Yi Mon (2023)
The ongoing Covid-19 pandemic has led to a global health crisis and the global financial crisis. This study examines the impact of the Covid-19 pandemic on the financial performance of Singapore-listed companies, based on a sample of 247 companies across 20 industries on the Singapore Stock Exchange for half-yearly periods from 2019 to 2021. I apply a regression model with multiple linear analysis, and paired t-test to analyze the financial performance impact of the Covid-19 pandemic across the sectors. According to the study's findings, the pandemic had impacted the financial performance of listed companies in Singapore and the impact varied from sector to sector. The most effected sectors were the services sectors. The findings of the study provide sufficient guidance to vital business performance issues. These results will help researchers and investors better understand how the unexpected health crisis affected the financial performance of Singapore listed companies.